The Strategy of Paratransgenesis for the Control of Malaria Transmission - Fofana, Aminata; Yerbanga, Rakiswendé Serge; Bilgo, Etienne; Ouedraogo, Georges Anicet; Gendrin, Mathilde; Ouedraogo, Jean-Bosco (Frontiers in Tropical Diseases, 2022)
Insect-borne diseases are responsible for important burdens on health worldwide particularly in Africa. Malaria alone causes close to half a million deaths every year, mostly in developing, tropical and subtropical countries, with 94% of the global deaths in 2019 occurring in the WHO African region. Considering the lack of an effective malaria vaccine and the resistance of parasites to drugs and of mosquitoes to insecticides, the need for novel strategies to control or stop the transmission of the disease is pressing. In recent years, several studies have focused on the interaction of malaria parasites, bacteria and their insect vectors. Their findings suggested that the microbiota of mosquitoes could be used to block Plasmodium transmission. This strategy, termed paratransgenesis, aims to interfere with the development of malaria parasites within their vectors through genetically-modified microbes, which produce antimalarial effectors inside the insect host. Here we review the progress of the paratransgenesis approach, and the challenges of stable introduction of transgenes, for an effective application to fight against malaria, which remains devastating in endemic areas.